‘Chickens, Crops, and Tractors’: The Use of Machines as Sacred Resource in Mennonite Fresh Air Hosting Programs - Shearer, Tobin Miller (Journal for the study of religion, nature and culture, 2010)
This essay argues that machines filled a sacred purpose in the middle of the twentieth century that has gone unrecognized by scholars of religion. The Mennonites who hosted African-American children from urban environments for one- to two-week stays in the country used tractors to promote their religious Fresh Air programs. From 1950 through 1979, tractors also figured prominently in the children’s testimonies about their rural sojourns. Fresh Air hosts, promoters, and participants thus used a diesel-powered machine for religious ends and, in so doing, featured an industrialized product as a symbol of a natural retreat. Mennonite Fresh Air programs also reveal similarities between the city and country that religious and secular narratives of the period have obscured. Scholarship in the tradition of Leo Marx will be enriched by shifting attention from the chronology of machine-based industrialization to the uses of machines in natural settings for religious purposes.